Pengaruh Sistem Pengendalian Internal Pemerintah dan Komitmen Organisasi Terhadap Kualitas Laporan Keuangan Daerah - Nur Chabibah; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2023)
This study aims to determine the government's internal control system and organizational influence of regional financial reports. Questionnaire distribution method is the type of research used. SPSS software is used to process data in this study. The sample in this study were employees who worked at the Malang City Service Office, totaling 35 people. The validity and reliability requirements have been met by this research. Checking the information used in this study is the investigation of factual explanations, old-style presumption tests, different linear relapses, speculation tests and investigation of the coefficient of guarantee. The variables used in this study are the independent va requirements have been met by this research. Checking the information while the dependent variable requirements have been met by this research. information of regional financial. the results of this study concluded that the government's internal control system and organizational commitment have a positive effect on the quality of financial reports partially or simultaneously.Keywords: Government internal control system, organizational commitment, quality of regional financial reports